How do you evaluate (d+1)(d-1+6) d=2?
1 Answer
Oct 15, 2015
The answer is 21
Explanation:
How to get the answer:
- Replace the variable with the value
=> (2+1)(2-1+6) - First you would do
(2+1)=3 - The problem is now
(3)(2-1+6) - Now you do
2-1 . You do this instead of doing1+6 because you do subtraction and addition from left to right - Then you have
(3)(1+6) =(3)(7) - Parentheses tell you to multiply so the answer you should get is twenty-one
I took a picture of the elongated steps because I describe how to solve inside the parentheses